2022
DOI: 10.3390/children9040461
|View full text |Cite
|
Sign up to set email alerts
|

Health Economic Aspects of Childhood Excess Weight: A Structured Review

Abstract: An economic perspective is crucial to understand the broad consequences of childhood excess weight (CEW). These can manifest in the form of elevated health care and societal costs, impaired health status, or inefficiencies in the allocation of resources targeted at its prevention, management, or treatment. Although existing systematic reviews provide summaries of distinct economic research strands covering CEW, they have a restricted focus that overlooks relevant evidence. The overarching aim of this structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 164 publications
0
2
0
Order By: Relevance
“…This study was registered in the PROSPERO database of systematic review protocols (registration number: CRD42021267540). 25 We conducted systematic searches from the inception of each search engine to August 5, 2021, and updated the searches on April 19, 2023, (1900-present). The searches were built using title/abstract keywords, subject headings, or MeSH terms, where available, for the following key concepts: obesity/overweight and exercise/dietary interventions and childhood terms and economic/cost terms.…”
Section: Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…This study was registered in the PROSPERO database of systematic review protocols (registration number: CRD42021267540). 25 We conducted systematic searches from the inception of each search engine to August 5, 2021, and updated the searches on April 19, 2023, (1900-present). The searches were built using title/abstract keywords, subject headings, or MeSH terms, where available, for the following key concepts: obesity/overweight and exercise/dietary interventions and childhood terms and economic/cost terms.…”
Section: Search Strategymentioning
confidence: 99%
“…However, it excluded surgical interventions. Our updated searches, as part of a structured review, 15 identified 31 additional studies since the systematic review by Zanganeh et al 9 Furthermore, two other recent systematic reviews were either focused solely on school‐based interventions 16 or preventive interventions with dietary components only, 17 highlighting the need for a systematic review of the evidence that is broader in reach.…”
Section: Introductionmentioning
confidence: 99%